Institutional Marketing Effectiveness on Students Admission Process (International Journal of Food and Nutritional Sciences, 2022)
This research paper investigates the impact of institutional marketing strategies on students' decision-making process when considering admission to management courses at Savitribai Phule Pune University (SPPU). The study focuses specifically on MBA students and aims to understand the influence of various marketing strategies employed by SPPU in attracting and engaging prospective applicants. The research design adopts a quantitative approach, utilizing a cross-sectional survey to collect data from a sample size of 400 MBA students. The study examines the perceived impact of marketing strategies on students' decision-making, the importance of marketing efforts in shaping their perception of SPPU's management courses, and the effectiveness of marketing strategies in communicating the strengths and advantages of the programs. The findings indicate that the marketing strategies employed by SPPU have a significant positive influence on students' decision-making, with a majority agreeing that these strategies played a role in considering SPPU as their preferred institution. The study also highlights the importance of marketing efforts in shaping students' perception of SPPU's management courses, as well as their effectiveness in effectively communicating the institution's strengths. Furthermore, the study reveals the pivotal role of digital marketing efforts in exposing students to SPPU's marketing initiatives and impacting their perception and decision-making process. The research contributes to the existing body of knowledge on institutional marketing strategies in the higher education sector and provides valuable insights for SPPU and other institutions in designing effective marketing campaigns to attract and engage prospective MBA students. The limitations of the study and future research directions are also discussed.